Management Strategies Of Madrasah Supervisors To Improve The Performance And Motivation Of Madrasah Principals And Teachers In Mas Yaspi Labuhan Deli Medan City - Sulasmi, Sulasmi; Rafida, Tien; Fadhli, Muhammad (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to improve the performance and motivation of madrasah principals and teachers, especially in Madrasah Aliyah Swasta YASPI Labuhan Deli Medan City, and can provide insight in implementing strategic management for other madrasahs. This study used a qualitative research approach to collect data through interviews, observations, and documentation studies. The results showed that madrasah supervisors in MAS YASPI Labuhan Deli Kota Medan have adopted a series of strategies that have proven effective in improving the performance and motivation of madrasah heads and teachers. Through simple steps such as needs analysis, communication, collaboration, goal setting, training, coaching, and rewards, they have succeeded in stimulating growth and progress in the educational environment. Strategy implementation is done through a process that involves open communication, performance observation, active collaboration, and support and recognition of achievements. Evaluation of the strategy is done systematically by assessing success in achieving goals, identifying shortcomings and providing guidance for improvement. Thus, madrasah supervisors not only act as supervisors, but also as leaders and facilitators who help improve the quality of education in MAS YASPI Labuhan Deli Medan City, making the environment more productive and developed.